Sharing knowledge on the sustainable business model: An aquaculture start-up case in Thailand - Montiean Pornparnomchai (2022)
Given the growing population and consumption, coupled with limited resources, sustainable ways of living are gaining importance in the modern world. This study aims to share knowledge regarding practices for transitioning from traditional business model (TBM) to sustainable business model (SBM) based on design thinking process and sustainability. An early-stage fish-cage aquaculture start-up (FCAS) in Thailand is used as our case study. The study adopts the descriptive qualitative case study approach. Design thinking, sustainability, and lean business model canvas (LBMC) are used as well. Data are collected from 15 participants including customers and stakeholders, using semi-structured interviews, field interviews, focus group discussions, and pilot testing. Direct content method is used to analyse data at the firm-level. Data triangulation helped improve completeness of findings. The results highlight that SBM, adapted from the LBMC, and its contributions can be used to share and reflect new knowledge on understanding of FCASs in Thailand.